The Role of Farmer Partnership in Patchile Business in Karya Bhakti Village Kulisusu Barat District North Buton Regency - Hasyanky M Saragi; La Ode Alwi; Samsul Alam Fyka (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2022)
The problem faced by farmer patchouli in the countryside regarding the lack of capital for farming. Farmer patchouli resolved the problem by choosing a partner with the owner of capital because the process is no capital loan complicated and no use bound contract. Study this aim for knowing pattern partnership and the attachment among capital owner and farmer partner patchouli and knowing income farmer partner and income owner of capital in village Karya Bhakti districts West Kulisusu District North Buton. Karya Bhakti village is the wrong centre for farming patchouli. They were chosen in August-September 2021 as the location for research. The study used 27 respondents as the sample. The research variables in this study are the respondents' age, education, farm experience and family dependents—the partnership pattern between the owner of the capital and the farmer. Attachment of capital owner to patchouli farmer is trust, networks and norms. Technical data retrieval is done by observation, interview and summarizes the answer. Analysis data used descriptive analysis and qualitative descriptive analysis. Partnership systems applied by capital owners with farmer partners in village Karya Bhakti tend to follow a pattern of cooperation in operational agribusiness (KOA). Owners of capital and farmers have rights and obligations. The obligation and right of the capital owner are to provide capital loans and receive farmer crops. The farmer's obligations are to receive capital loans and provide land and crops to the owner capital. The entanglement is influenced by the existence of social capital, which consists of trust, network, and norms so that the partnership can continue. Partnership by owner capital and farmer is based on mutual trust.